Strategi Dakwah Muhammadiyah Melalui FKMMS (Forum Komunikasi Masjid Muhammadiyah Sidoarjo) - Istkomah, Istkomah; Romadlon, Dzulfikar Akbar; Hariyanto, Budi (Fakultas Dakwah IAIN Purwokerto, 2020)
The focus of Muhammadiyah, as stated in its AD/ART, is the da'wa of Islam